A phytochemical investigation of homalium ceylanicum - Opinya A. Ekabo (2018)
Vacciniin [4] (6-O-benzoyl-d-glucopyranoside) and two new benzenoid glucosides, homaloside a [1] (1″-O-benzyl-3″-O-benzoyl-α-L-arabinopyranosyl(1‴↦4″)-′-d-glucopyranoside) and homaloside D [2] [1-(1′-hydroxy-6′-oxocyclohex-2′-ene-carboxymethyl)-5-hydroxyphenyl-6″-O-benzoyl-′-d-glucopyranoside], were isolated from the n-BuOH fraction of Homalium ceylanicum (Flacourtiaceae). a novel cyclohexenone carboxylic acid ester, 1-hydroxy-6-oxocyclohex-2-enoic acid methyl ester [3], was also isolated from this fraction. The structures were elucidated by chemical and nmr (COLOC, FLOCK, and selective INEPT) techniques. © 1993, American Chemical Society. All rights reserved.